O desenho do lugar, a paisagem da favela - Pereira, Rafael Carvalho Fernandes (2024)
The resident’s daily actions in constructing the favela show us a different model of spatial conception and organization, reflected in the landscape and the occupation of spaces. Since the beginning of documenting these spaces in Brazil, authorities have attempted to eradicate this ‘other’ place in the city by implementing pre-established housing models and resettling residents to distant areas. These actions aimed to establish a hegemonic order and coherence, crystallizing local actions and imposing material forms as instruments of control and hygiene of urban life. However, in some cases, the fundamental characteristics of favela life resurface within these Cartesian housing models, and with this, they perpetuate the resident’s feeling of belonging and identification with their home and collective space. Within this proposal for a ‘formal’ city, the favela re-emerges as an alternative for urban dynamics, but also as resistance. The research is based on the case of Favela das Quadras, located in the Aldeota neighborhood in Fortaleza, initially as a spontaneous settlement in the 1950s, and underwent intervention by the State with the implementation of a housing model between 1980 and 1986, subsequently receiving the name of the São Vicente de Paulo Housing Complex. More than 30 years later, the place shows us signs of reappropriation of residents through housing modifications adapting to the needs of each family. This research uses the concepts of landscape and place as a way of approaching communication and the sociocultural identification of a space of memory for the local population. The methodology tools seek to measure within a qualitative-quantitative approach the identification of residents with their place through semi-structured interviews, production of graphic materials by residents, analysis of the evolution of the landscape through local interventions and questionnaires, with the aim of generating a general overview of the activities carried out locally and how they physically and cognitively modify the place. Finally, the discussion about the dynamic condition of the favela continually redefining and reformulating the spaces of the Housing Complex is of fundamental importance for understanding its role in the city as places for the reproduction of life.